2016
DOI: 10.4251/wjgo.v8.i4.330
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as diagnostic and prognostic biomarkers in colorectal cancer

Abstract: MicroRNAs (miRNAs) are key regulators involved in various tumors. They regulate cell cycle, apoptosis and cancer stemness, metastasis and chemoresistance by controlling their target gene expressions. Here, we mainly discuss the potential uses of miRNAs in colorectal cancer (CRC) diagnosis. We also shed light on the important corresponding miRNA targets and on the major regulators of miRNAs. Furthermore, we discuss miRNA activity in assessing the prognosis and recurrence of CRC as well as in modulating responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 98 publications
1
33
0
Order By: Relevance
“…Extensive research effort has been conducted recently to investigate the potential of using miRNAs as biomarkers for diagnosis, tumor stage as well as for predicting patients’ outcome [48,49,50]. MiRNAs present unique features such as high tissue specificity, good sensitivity and stability.…”
Section: Colorectal Cancer and Mirnamentioning
confidence: 99%
“…Extensive research effort has been conducted recently to investigate the potential of using miRNAs as biomarkers for diagnosis, tumor stage as well as for predicting patients’ outcome [48,49,50]. MiRNAs present unique features such as high tissue specificity, good sensitivity and stability.…”
Section: Colorectal Cancer and Mirnamentioning
confidence: 99%
“…MicroRNAs are a kind of short and single stranded RNAs which can suppress target genes by targeting the 3′‐untranslated regions (3′‐UTR) of mRNAs (Muhammad et al, ). miRNAs can control a lot of important cell processes such as cell proliferation, apoptosis, cell cycle arrest, and invasion (Shea et al, ; Yi et al, ). Recently, microRNAs (miRNAs) have been recognized as significant markers in various cancers (Berindan‐Neagoe & Calin, ; Gu et al, ; Sun & Lai, ).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs not only serve crucial roles in regulating various fundamental cellular processes but are also closely associated with tumorigenesis and tumor development (10,11). Previous studies have reported that miRNAs are aberrantly expressed in almost all types of human cancer, including PTC (12), colorectal cancer (13), lung cancer (14), glioblastoma (15) MicroRNA-766 inhibits papillary thyroid cancer progression by directly targeting insulin receptor substrate 2 and regulating the PI3K/Akt pathway and bladder cancer (16). Increasing evidence has revealed that various miRNAs are differentially expressed in PTC, and their dysregulation has been implicated in the regulation of PTC occurrence and development (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%